A dual-porosity model for analysis of temperature effects on hydro-mechanical behaviour of GMZ bentonite under unconfined conditions. (February 2023) - Ni, Hongyang; Liu, Jiangfeng; Jivkov, Andrey P.; Shen, Wanqing; Shao, Jianfu
Abstract: A model for coupling thermal, hydraulic, and mechanical properties of GMZ bentonite is presented. The model considers a binary classification of the pores into macropores and micropores and describes the effect of the changes in the two classes under free swelling conditions on the bentonite water retention behaviour. The macropores are assumed to be water conduits, while the water occupying the micropores is assumed to be immobile. The effects of temperature on the mobile and immobile water are considered separately. Variation of mobile water is determined by the water retention curve considering temperature effects, and immobile water is calculated from the deformation of micropores due to different relative humidities (RHs) and temperatures. The model is used to simulate free swelling tests of GMZ bentonite carried out from low RH to high RH under different temperature conditions. A comparison with available experimental data shows that the model offers a good predictive capability and can be used for further understanding the temperature effects on the hydraulic-mechanical behaviour of bentonite. The work underpins engineering assessments of the GMZ bentonite behaviour required for the construction of the deep geological repository at Beishan under coupled thermo-hydro-mechanical effects.